PENGORGANISASIAN DAN ANALISIS USAHA PERIKANAN KERAMBA DI WADUK PLTA KOTO PANJANG KABUPATEN KAMPAR - Tibrani '; Tince Sofyani (Berkala Perikanan Terubuk, 2010)
The aims of the research are : 1). to analyze social-economic condition offishfarmer’s floating net culture at Dam of PLTA Koto Panjang ,2). to analyzethe business of floating net culture at Dam of PLTA Koto Panjang 3). toanalyze the extended program and result support marketing.This study use survey method in three sample villages, that is PongkaiIstiqomah, Koto Tuo and Tanjung Alai Village. The data collected fromfishfarmer of floating net by sensus of 30 fishfarmer”s floating net culture. Datawere analyzing by descriptive method. To show feasibility study , financialanalysis were used.Result of this study showed that floating net culture at Dam of PLTA KotoPanjang did as a group activity whereas group organization by Fishery AffairsService of Kampar Regency. Average age of fishfarmer’s floating net is inproductivity age, average total family account is 5 person, most of fishfarmereducation are elementary level and junior high school, their primary activity are asa rubber farmer and fisherman. Average capital of floating net unit with size4x3x2 meter is Rp 4,838,710, average offishfarmer’s profit is Rp1,223,950/harvest or Rp 421,580 /month. BCR =1.38, FRR=25.29 andPPC=3.95. Therefore, the business of floating net culture can be continued. Thefloating net culture at Dam of PLTA Koto Panjang is one of the group activitythat have never a loan by local government of Riau Province. Marketing fish inthis area supporting by local geography with road condition which can entered byall kind of vehicles until to remote area and it make seller easier in transportmaterial.